Problematika Pernikahan Generasi Milenial Terhadap Kasta Di Bali - G. A. Amanda Kristina Damayanti (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2020)
Catur Warna is four things that become a choice of life in the classification of society based on one's talent (expertise)/ expertise and skills (karma)/profession. But the invaders exploited the innocence of the community by giving a wrong understanding about the classification of this society. Castes is used by using varna chess which in its application is very different from the meaning in the scriptures. This misunderstanding continues to this day which causes a lot of disputes that occur in the Balinese Hindu community due to the lack of understanding and knowledge of studying the Scriptures. But as the development of civilization and technology does not make this a complicated thing, because everyone can easily get information. In this sophisticated era, there are no difficult boundaries, including those living in this era, known as the millennial era, where all groups have interconnected with one another. Related to making it easier for generations to find successful friends both online and offline, there is no limit to the distance of all easily obtained but the customs and customs that are still needed to be a challenge. There are still many who uphold the cultural heritage to this day which makes castes and varna a challenge that continues to occur today. the existence of this castes is also not a fateful thing because it has ingrained with the identity and characteristics of the area of ​​origin by not applying the principle of ruling castes.